PENGARUH RASIO LANCAR DAN PENGEMBALIAN ASET TERHADAP PERTUMBUHAN LABA DI PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN - Adiya Lestari; Irawan Noor (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2023)
This study aims to determine and analyze the effect of current ratio and return on assets on profit growth in food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The type of data in this study is secondary data in the form of company financial statements. Based on purposive sampling techniques, samples were obtained from food and beverage sub-sector companies. The analysis method used is multiple and simple linear regression. Based on the results of the study shows that the current ratio does not have a significant effect on profit growth. Return on assets has a positive and significant effect on profit growth.